Interioritas Ruang Gerak Membaca Literatur Fiksi Ergodik House of Leaves .docx - Coriesta Dian Sulistiani; Hanifah Azzahra (Universitas Multimedia Nusantara, 2020)
Ergodic fiction literature is different from other fiction literature. Ergodic literature elements determine the space of the reader. It affects the reader to move that is not limited to the hand and eye movements, but also spatial movements of other limbs. This paper discusses the interiority that occurs behind the body space of readers of ergodic fiction literature. Through a qualitative analysis of the mapping of body space in reading the ergodic literature of Mark Z Danielewski’s House of Leaves (2000), the result shows that elements of ergodic fiction such as narration, nodes, options, multiple paths, and peritext are part of the interiority of space.